A diagnostic detour: A case of Lemierre syndrome diagnosed after inconclusive CT venogram - Amanda Essebag; Rachel Beaudoin; Vicky Tagalakis (Canadian Journal of General Internal Medicine, 2026)
Abstract Lemierre syndrome is a rare, life-threatening complication of oropharyngeal infections. We report the case of a 19-year-old man with fever, pharyngitis, and hypoxemia. Our case illustrates how indeterminate imaging initially diverted diagnosis, highlighting the need for a high index of suspicion and consideration of complementary imaging modalities for timely recognition and management of this potentially fatal condition.